Second harmonic generation by diode-pumped solid state laser system - Nurkhaizan Zulkepli, 1987-; Noriah Bidin, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010